Islam Dot Com: Contemporary Islamic Discourses in Cyberspace by Mohammed el-Nawawy and Sahar Khamis (New York: Palgrave Macmillan, 2009. 280 pages.) (American Journal of Islam and Society, 2010)
The articulation of Islam with the new media, and the Internet in particular,has attracted the interest of many researchers. The Internet’s openness anddemocratic potential may infuse Islamic discourses with a new dynamic or,alternatively, offer a new lease of life to such valued traditions as shura (consultation)and ijtihad (independent thinking). Islam Dot Com belongs to theline of thought that seeks to discover how the Internet has been associatedwith Islam and the extent to which it may be thought to contribute to itsdemocratization by providing a truly public sphere in which interested peoplecan participate. On the other hand, the authors are cognizant of the limitationsof the concept of “public sphere” when applied to Islamic contexts.Part of the book’s remit, therefore, is to examine how the Internet relates to shura, ijtihad, and ijma` (consensus). At the same time, it seeks to relatethese theoretical arguments to an empirical case study consisting of a textualanalysis of three Islamic websites: www.islamonline.net, www.amrkhaled.net, and www.islamway.com. The book’s structure comprises threetheoretical chapters (chapters 1-3), two empirical chapters (chapters 4 and5), and a concluding chapter (chapter 6) ...